(untitled) (Research, Society and Development, 2020)
This study aims to understand the training project for students of the State School of Professional Education - EEEP Professor Lysia Pimentel Gomes Sampaio Sales, located in Sobral, Ceará. For this, we analyzed, based on the method of qualitative dialectical material of nature, the Pedagogical Political Project of the Teaching Unit, having as reference the concepts of work as Educational Principles, Sciences, Technology and Culture (the structured mechanisms of the High School). General Curriculum Guidelines for Basic Education. We find that the school is a privileged space to study as disputes fought in worker training, because no document is found, conceptions that both privilege the integral formation of the student, as elements that meet the training and compromise of working class interests.